Isolation of genes related to heterocyclic compounds degradation from marine bacteria - Rachel Showney, Unga (Universiti Malaysia Sarawak (UNIMAS), 2012)
Bioremediation is a technology applied to clean polluted sites with the use of microorganisms, particularly marine ecosystem. Heterocyclic compound is known to be potential pollutant to the environment, and its distribution is mainly due to human activities. The degradation process occurs as marine bacteria utilizing the heterocyclic compound as their carbon and nitrogen sources, thus producing safer by-products. The present study was focused on the isolation of degradative genes related to carbazole and biphenyl, the heterocyclic compound derivatives, from marine bacteria total DNA using Polymerase Chain Reaction (PCR) and DNA sequencing strategies. The degradation related genes were isolated by using primers design based on previously reported genes. The PCR products were sent to 1st Base Laboratory for sequencing. However except for the control sample 16S, the sequences data obtained were too ambiguous and did not provide good result for nucleotide comparison. Analysis by BLAST software of the 16S sequence data showed the marine bacterium was identified as Paracoccus seriniphilus.